1925 Ind. Acts 499, § 13 - (:unkn) unknown (My University, 1925)
Prohibited changing, altering, removing, or obliterating identifying information on any pistol or revolver. Possession of such arms is a misdemeanor, punished by imprisonment for not less than six months nor more than one year.
Keywords: DEFACED FIREARMS